The Impact of Social Connectedness and Internalized Transphobic Stigma on Self-Esteem Among Transgender and Gender Non-Conforming Adults. Issue 6 (12th May 2017) - Austin, Ashley; Goodman, Revital
ABSTRACT: The transgender and gender non-conforming (TGNC) community continues to represent a notably marginalized population exposed to pervasive discrimination, microaggressions, and victimization. Congruent with the minority stress model, TGNC individuals persistently experience barriers to wellbeing in contemporary society; however, research uncovering resilience-based pathways to health among this population is sparse. This study aimed to explore the impact and interaction between internalized transphobic stigma and a potential buffer against minority stress—social connectedness—on the self-esteem of TGNC identified adults. Data were collected from 65 TGNC identified adults during a national transgender conference. Multiple regression analysis reveals that self-esteem is negatively impacted by internalized transphobia and positively impacted by social connectedness. Social connectedness did not significantly moderate the relationship between internalized transphobia and self-esteem. Micro and macro interventions aimed at increasing social connectedness and decreasing internalized transphobic stigma may be paramount for enhancing resiliency and wellbeing in the TGNC community.